Ciencia Para Todos: Guías Para Superar Los Desafíos de la Comunicación Científica en Casos de Comunicación de la Salud - Denisse VÁSQUEZ-GUEVARA (Fonseca, Journal of Communication, 2023)
This study explores the science communication models of deficit and dialogue and their results in prior research. The theoretical framework presented in this study informs the overall study’s methodology with suggestions for participatory action research studies in the practice and research of science communication.